Investigation of the apoptosis‐inducing effect of docetaxel by comprehensive LC–MS–based metabolomics and network pharmacology approaches. (10th June 2022) - Wang, Dongyao; Tang, Yuxiao; Feng, Fei; Qi, Minyu; Fang, Jiahao; Zhang, Ying; Chai, Yifeng; Cao, Yan; Lv, Diya
Abstract: Docetaxel is one of the clinical first‐line drugs and its combination with other chemotherapy agents for advanced or metastatic cancers has attracted widespread attention. Therefore, to promote the clinical application of docetaxel alone or in combination, a comprehensive investigation of the metabolic mechanism of docetaxel is of great importance. Here, we apply an integrative analysis of metabolomics and network pharmacology to elucidate the underlying mechanisms of docetaxel. After taking the intersection of the aforesaid two methods, five pathways including ABC (ATP‐binding cassette) transporters, central carbon metabolism in cancer, glycolysis and gluconeogenesis, cysteine and methionine metabolism, and arginine biosynthesis have been screened. Concerning the interaction network of these pathways and the anti‐apoptosis effect of docetaxel itself, the central carbon metabolism in cancer pathway was mainly focused on. This study may help delineate global landscapes of cellular protein–metabolite interactions, to provide molecular insights about their mechanisms of action as well as to promote their clinical applications.